2014
DOI: 10.21273/hortsci.49.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Alcohol Application to Control Meristematic Regrowth in Bottle Gourd and Interspecific Hybrid Squash Rootstocks Used for Grafting Watermelon

Abstract: Application of fatty alcohol compounds to rootstock meristems can control rootstock meristematic regrowth, thus decreasing the cost of producing grafted watermelon transplants by reducing the labor. Eight rates of Fair 85 Ò and Off-Shoot T Ò , two commercially available fatty alcohol compounds, were applied to the meristem region of bottle gourd (Lagenaria sicereria cv. Emphasis) and interspecific hybrid squash (Cucurbita maxima 3 Cucurbita moschata cv. Carnivor) rootstocks to determine the optimal application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 13 publications
4
34
0
Order By: Relevance
“…Shortly after emergence, when cotyledons had turned upward and fully opened, rootstock apical meristems were treated with 25 mL of a 6.25% dilution of a sucker control agent (Fair 85 Ò fatty; Fair Products, Cary, NC). The sucker control agent effectively killed rootstock meristematic tissue, preventing rootstock regrowth after grafting (Daley and Hassell, 2014). Twenty-four hours before grafting, plants were placed indoors in a room with limited light and were adjusted to 68°F to slow photosynthesis and metabolic activity.…”
Section: Methodsmentioning
confidence: 99%
“…Shortly after emergence, when cotyledons had turned upward and fully opened, rootstock apical meristems were treated with 25 mL of a 6.25% dilution of a sucker control agent (Fair 85 Ò fatty; Fair Products, Cary, NC). The sucker control agent effectively killed rootstock meristematic tissue, preventing rootstock regrowth after grafting (Daley and Hassell, 2014). Twenty-four hours before grafting, plants were placed indoors in a room with limited light and were adjusted to 68°F to slow photosynthesis and metabolic activity.…”
Section: Methodsmentioning
confidence: 99%
“…Rather than putting energy into new growth, carbohydrates are stored in the hypocotyl and cotyledons of the rootstocks. Previous experiments have revealed a starch increase of 100and 200-fold in hypocotyls of bottle gourd and interspecific hybrid squash rootstocks, respectively, over 21 d after fatty alcohol treatment (Daley et al, 2014). We hypothesize that this increase of stored energy in the rootstock could be harnessed by the plant to improve current grafting methods by providing sufficient energy to increase graft survival, rootstock rooting, and overall grafted transplant quality.…”
mentioning
confidence: 83%
“…Manual meristem removal often removes the meristem only partially, allowing meristem regeneration to occur. Previous studies have demonstrated the success of fatty alcohol rootstock treatments in controlling meristematic regrowth (Daley and Hassell, 2014). Fatty alcohol products are traditionally used in tobacco (Nicotiana tabacum) production to remove axillary meristems and promote growth of remaining leaves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Topping and sucker control of tobacco improves yield and the concentration of nicotine of leaf to be harvested, by reducing the competition of nutrients (Moore, 2012). Also a commercial fatty alcohol compound used on tobacco was recently demonstrated to be a part of new grafting method for watermelon (Citrullus lanatus), controlling rootstock shoot regrowth while preparing seedlings (Daley, 2014;Daley and Hassell, 2014). For tomato, Maw (1977) demonstrated effective use of fatty alcohol for controlling axillary shoot on tomato plants grown in greenhouse, although the fatty alcohol had to be applied exclusively to the axillary shoots otherwise it caused chemical damage on leaves and stems.…”
mentioning
confidence: 99%